Analisis Kandungan Logam pada Tumbuhan Dominan di Lahan dan Kolong Pasca Penambangan Timah Bangka Selatan - Eka Sari; Dyah Sandra Fiona; Nuril Hidayati; Eddy Nurtjahya (PROMINE, 2017)
Besides to impact on changing of landscape and biodiversity, tin mined left heavy metal contaminants,and phytoremediation (the use of plants to accumulate heavy metals) is a chosen method. This studymeasures Pb (Lead), Cu (Copper), Zn (Zinc) in soil and dominant terestrial plants in tin mined landand Fe (Iron), Al (Aluminum), As (Arsen) in root and shoot of dominant plants in ex-tin mined pond.Dominant species was determined by vegetation analysis of quadrate method. Metals analysis wasconducted using atomic absorption spectrophotometry. Pb in secondary forest (8 ppm), in revegetatedtin mined soil (10,80 ppm) and in 0 year abandoned tin mined soil) (20,70 ppm) exceed qualitystandards. There is no potential of becoming accumulator plant for Pb, Cu, Zn in tin mined land, butSchima wallichii was found potential to be Cu accumulator in secondary forest because it hastranslocation factor (TF)>1. The highest Fe > 2% in shoot and > 3% in roots. Al > 2% in shoot and >3% in root. As was not detected.Keywords: Tin mined soil, Bangka, Metal, Accumulator plants